2004
DOI: 10.1074/jbc.c300488200
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Conformation of Myosin V

Abstract: We have found that myosin V, an important actinbased vesicle transporter, has a folded conformation that is coupled to inhibition of its enzymatic activity in the absence of cargo and Ca 2؉ . In the absence of Ca 2؉where the actin-activated MgATPase activity is low, purified brain myosin V sediments in the analytical ultracentrifuge at 14 S as opposed to 11 S in the presence of Ca 2؉ where the activity is high. At high ionic strength it sediments at 10 S independent of Ca 2؉ , and its regulation is poor. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
161
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 39 publications
10
161
1
1
Order By: Relevance
“…It has been shown that the activation of myosin Va by Ca 2ϩ is accompanied by a transition from a folded conformation (14S in the absence of Ca 2ϩ ) to an open conformations (11S in the presence of Ca 2ϩ ) (6)(7)(8). We took two approaches to investigate the effect of D134A and D136A mutations on the conformational changes of myosin Va.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the activation of myosin Va by Ca 2ϩ is accompanied by a transition from a folded conformation (14S in the absence of Ca 2ϩ ) to an open conformations (11S in the presence of Ca 2ϩ ) (6)(7)(8). We took two approaches to investigate the effect of D134A and D136A mutations on the conformational changes of myosin Va.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that Ca 2ϩ -activation of the ATPase activity of myosin-Va is accompanied by a large conformational transition, from a 14S folded conformation in the absence of Ca 2ϩ to an 11S open conformation in the presence of micromolar Ca 2ϩ (6)(7)(8). In contrast, myosin Va heavy meromyosin (HMM), a constitutively active fragment lacking the C-terminal globular tail domain, is not well regulated by Ca 2ϩ and does not undergo a large conformational transition like fulllength myosin Va (6)(7)(8). These results suggest that the tail domain plays a key role in the Ca 2ϩ -dependent regulation of myosin Va by inhibiting the ATPase of the head.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with some class II myosins, for which the lever arm plays a regulatory function, it is plausible that the LCBD of myosin V also serves a regulatory role. In agreement with this view, a number of reports uncover a regulatory effect of Ca 2ϩ and CaM on the conformation and activity of myosin V that could involve the LCBD directly (21)(22)(23)(24)(25). Inhibition of the ATPase activity of myosin V after increases in Ca 2ϩ concentration has been attributed to the dissociation of CaM from the heavy chain (26) and͞or a conformational change in CaM (27).…”
mentioning
confidence: 79%
“…Our results suggest that this complex modulates SNARE-dependent interactions and regulates at least the exocytosis of dense-core vesicles by forming a link between vesicles and their targets; in other words, the complex regulates the recruitment of the vesicles to the readily releasable pool during sustained secretion. Recently, the Ca 2ϩ /CaM-dependent interaction between the cargo-conveying tail and the head of myosin-Va was shown to be an important factor regulating its conformation (Krementsov et al, 2004;Li et al, 2004Li et al, , 2005Wang et al, 2004). Ca 2ϩ /CaM is an important regulator of both exocytosis and the cargo-conveying activity of myosin-Va, and further studies of this novel interaction should help elucidate the roles of myosin-Va in Ca 2ϩ -regulated exocytosis.…”
Section: Discussionmentioning
confidence: 99%